Postanaesthetic shivering – from pathophysiology to prevention - Bermudez Lopez, Maria (Romanian journal of anaesthesia and intensive care, 2018)
Postoperative shivering is a common complication of anaesthesia. Shivering is believed to increase oxygen consumption, increase the risk of hypoxemia, induce lactic acidosis, and catecholamine release. Therefore, it might increase the postoperative complications especially in high-risk patients. Moreover, shivering is one of the leading causes of discomfort for postsurgical patients. Shivering is usually triggered by hypothermia. However, it occurs even in normothermic patients during the perioperative period. The aetiology of shivering has been understood insufficiently. Another potential mechanism is pain and acute opioid withdrawal (especially with the use of short-acting narcotics). Besides that shivering is poorly understood, the gold standard for the treatment and prevention has not been defined yet. Perioperative hypothermia prevention is the first method to avoid shivering. Many therapeutic strategies for treating shivering exist and most are empiric. Unfortunately, the overall quality of the antishivering guidelines is low. Two main strategies are available: pharmacological and non-pharmacological antishivering methods. The combination of forced-air warming devices and intravenous meperidine is the most validated method. We also analysed different medications but final conclusion about the optimal antishivering medication is difficult to be drawn due to the lack of high-quality evidence. Nevertheless, control of PS is possible and clinically effective with simple pharmacological interventions combined with non pharmacological methods. However, to be consistent with the most up-to-date, evidence-based practice, future antishivering treatment protocols should optimize methodological rigor and transparency.